2020
DOI: 10.1515/npprj-2019-0033
|View full text |Cite
|
Sign up to set email alerts
|

Affecting the bonding between PLA fibrils and kraft pulp for improving paper dry-strength

Abstract: AbstractPolylactic acid fibrils (PLAf) were employed as a fiber component in papermaking. The addition of 5 wt % of PLAf to bleached kraft birch pulp increased the tensile index of the resulting 100 g/m2 paper sheets by 20 % in comparison to sheets produced without PLAf. By heat-treating the paper sheets containing 5 wt % PLAf, a 35 % higher tensile index in comparison to sheets produced without PLAf was achieved. SEM imaging showed that the heat-treatment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 20 publications
2
4
0
Order By: Relevance
“…6i, where the polylactic acid fibers and wood fibers were compressed to a flat shape and stacked compactly, forming a level and smooth plate layer on the paper surface. This transformation that happened on the composite paper surface is consistent with results of a previous study (Raunio et al 2020). In the study, it was found that polylactic acid fibers deform, melt, and flow around the plant fibers during the thermoforming treatment.…”
Section: Sem Analysis Of the Composite Paperssupporting
confidence: 93%
See 4 more Smart Citations
“…6i, where the polylactic acid fibers and wood fibers were compressed to a flat shape and stacked compactly, forming a level and smooth plate layer on the paper surface. This transformation that happened on the composite paper surface is consistent with results of a previous study (Raunio et al 2020). In the study, it was found that polylactic acid fibers deform, melt, and flow around the plant fibers during the thermoforming treatment.…”
Section: Sem Analysis Of the Composite Paperssupporting
confidence: 93%
“…These changes in the physical properties of the composite paper are consistent with previous studies (Yang et al 2019;Raunio et al 2020). In these studies, it was found that polylactic acid fibers can fill the pores and gaps in the paper due to heat conduction and pressure, thereby improving the density and mechanical properties of the composite paper.…”
Section: Effect Of Calendering On the Physical Properties Of The Composite Papersupporting
confidence: 90%
See 3 more Smart Citations